Organizational Culture and Motivation over Mediated Performance by Organizational Commitment - Syafriadi Cut Ali; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2019)
Public dissatisfaction with police detective's function has performed in conducting investigations, often makes the community not well served. A reports submitted does not necessarily revealed or fulfill a sense of justice. Therefore, the purpose in this study to assess the influence of organizational culture and motivation in police performance with mediated by organizational commitment. Here, we collect 195 respondents in police officers using Structural Equation Model (SEM). The results shows organizational culture influenced police performance, organizational culture influences organizational commitment, organizational commitment influenced police performance, motivation influenced organizational commitment and motivation influenced police performance.